Implementasi Perhatian Pengasuh Dalam Interaksi Sosial Pada Anak Panti Asuhan Hanifah III Gadut, Kec. Tilatang Kamang, Kab.Agam, Sumatera Barat - Ari Nasowaloon Harahap; Afrinaldi Afrinaldi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to explore and analyse the implementation of caregiver attention in children's social interaction at Hanifah III Gadut Orphanage, Tilatang Kamang District, Agam Regency, West Sumatra. The main focus of this research is to understand how caregivers at the orphanage provide attention to the children living there and how this affects their social interactions. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with caregivers, observation of the social interactions of children in the orphanage, and analysis of relevant documents. The results showed that caregivers' attention to children at Hanifah III Gadut Orphanage is very important in shaping healthy social interactions. The implementation of this attention includes psychological, emotional, and social aspects, all of which have an impact on children's development. In the context of orphanages, caregiver attention also has a significant role in forming interpersonal bonds between caregivers and foster children. This research is expected to provide further understanding of caregiving practices in orphanages and contribute to our understanding of the importance of mindfulness in shaping the social interactions of children living in such environments.